1999
DOI: 10.1063/1.125126
|View full text |Cite
|
Sign up to set email alerts
|

GaInNAs resonant-cavity-enhanced photodetector operating at 1.3 μm

Abstract: We demonstrate a GaAs-based p-i-n resonant-cavity-enhanced (RCE) GaInNAs photodetector operating near 1.3 μm. The device design was optimized using a transfer matrix method and experimental absorption spectra obtained from p-i-n structures grown without a resonant cavity. The RCE photodetector was fabricated in a single growth step by using GaAs/AlAs distributed Bragg reflectors for the top and bottom mirrors. A 72% quantum efficiency was obtained with a full width at half maximum of 11 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 13 publications
2
52
1
Order By: Relevance
“…Reports on the electrical characteristics and photoresponse of bulk Ga 1−x In x N y As 1−y diodes operating at wavelengths up to 1.3 m are limited to. [4][5][6][7] The p − i − n diodes reported in Ref. 6 had Ga 1−x In x N y As 1−y i regions up to 2 m thick, but the absorption edge was less than ϳ1.22 m and the reverse dark currents were measured for a limited field range up to 25 kV/cm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on the electrical characteristics and photoresponse of bulk Ga 1−x In x N y As 1−y diodes operating at wavelengths up to 1.3 m are limited to. [4][5][6][7] The p − i − n diodes reported in Ref. 6 had Ga 1−x In x N y As 1−y i regions up to 2 m thick, but the absorption edge was less than ϳ1.22 m and the reverse dark currents were measured for a limited field range up to 25 kV/cm.…”
Section: Introductionmentioning
confidence: 99%
“…1 It can therefore extend the photoresponse of GaAs-based optoelectronic devices to beyond 1.3 m, which previously could only be achieved by strained In x Ga 1−x As/ GaAs quantum wells or metamorphic InGaAs layers. 2 Hence, there is interest in using this material for GaAs-based photodetectors [3][4][5][6][7][8] and multijunction photovoltaic cells. 9,10 GaAs-based photodetectors can utilize highreflectivity AlAs/GaAs mirrors 4 and the Ga 1−x In x N y As 1−y material has been predicted to have low avalanche noise, 8 while photovoltaic cells can benefit from long wavelength absorption.…”
Section: Introductionmentioning
confidence: 99%
“…8 Based on this material system, lasing and light detection have been realized for the near infrared. [9][10][11][12] Recently, we presented a GaAs/AlGaAs resonant tunneling diode (RTD) with GaInNAs absorption layer for telecommunication light sensing with a sensitivity of 10 3 A/W, with the RTD serving as internal amplifier of weak electric signals, caused by photo-excited charge carriers. 13 RTDs with embedded quantum dots have even been demonstrated as single photon detectors for visible and near infrared wavelengths at cryogenic temperatures.…”
mentioning
confidence: 99%
“…One way to overcome this problem is to use a wider bandgap material such as , with consequently reduced tunnelling current. Recently, Heroux et al [7] showed that GaInAs alloyed with a dilute concentration of N and grown on a GaAs substrate strongly absorbs incident light at 1.3 m wavelength.…”
Section: Introductionmentioning
confidence: 99%